Tropical Foliage Plant Development: Breeding Techniques for Aglaonema and Dieffenbachia - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS, 2009)
ENH-1117, a 5-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes the techniques plant breeders can use for controlling flowering, effecting pollination, and securing seed production. Includes references. Published by the UF Department of Environmental Horticulture, May 2009.